Pentahelix Synergy in Halal Certification of Micro and Small Business Products at the Purwosari MSME Center - Aslikhah (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
This research aims to determine and analyze Pentahelix's synergy in implementing halal product certification for Micro, Small Enterprises (UMK) at the Purwosari UMKM Center (SEKAR). The increasingly urgent need for halal products in the global market makes halal certification an important aspect for the competitiveness of MSEs. Through a qualitative approach with in-depth interviews, participant observation, and document analysis, this research will investigate the interactions and roles of each Pentahelix pillar—government, micro and small industry players, academics, the SME community, and mass media—in supporting the implementation of halal certification for MSE products in the SEKAR community. The results of this research can provide in-depth insight into the contribution of each pillar and develop policy recommendations to strengthen the halal certification ecosystem for MSE products in the Purwosari MSME center. This research contributes to the literature on Pentahelix synergy and the implementation of halal certification at the Micro and Small Business level in Indonesia.